Financial system fragility models - Aurel Iancu (Romanian Academy, National Institute for Economic Research, 2011)
This paper analyses two types of models: 1. Those based on assumptions of monetary and financial market equilibrium disturbance in line with mainstream thinking that there is self-regulating market, the units would have rational expectations, and the crisis would be a temporary phenomenon caused by exogenous shocks. Here are the main objectives and features characteristic of the three generations of models; 2. Models based on financial instability hypothesis, taking into account both the dynamics of financial market as well as the role of uncertainty, interdependency and dynamic complexity. We present here Minsky's concept of financial instability and then analyse the content of some simplified models.
Keywords: C61; C62; C83; D84; E12; E13; E32; F44; 330; instability; model generations; balance sheet; hedge units; speculative units; Ponzi units; cyclical fluctuations; complexity